Structural differences arise between fruit cuticles of two apple cultivars during long term cold storage - Tóth, M.; Szabó, L.; Papp, I. (International Journal of Horticultural Science, 2018)
Apple fruits are covered by hydrophobic cuticle that provides protection against desiccation, pathogens, excessive water absorption and radiation. The features of cuticle affect the quality and storability of the fruits. It was aimed to evaluate the correlation between peel ultrastructure and weight loss in fruits covered by waxy bloom (cv. Florina) and without bloom (cv. Red Rome van Well) during 4-month cold storage. SEM (scanning electron microscopy) was used for visualization of the fruit surface and fruit weight was also measured. Several studies have revealed that there may be correlation between the ultrastructure of cuticle and its water permeability. Our results confirmed this phenomenon in case of two cultivars. The weight loss per fruit surface area unit of ‘Florina’ was found significantly higher than that of ‘Red Rome van Well’. At the same time the cuticular surface of the fruits contained more micro-cracks in case of the former cultivar. These data confirmed the relationship between the density of cuticular micro-cracks and the water vapour permeability. We concluded that this feature is more significant than the amount of natural waxy bloom on fruit surface.